Stereoselective Arene‐Forming Aldol Condensation: Catalyst‐Controlled Synthesis of Axially Chiral Compounds. Issue 53 (5th September 2017) - Witzig, Reto M.; Lotter, Dominik; Fäseke, Vincent C.; Sparr, Christof
Abstract: The fundamental role that aldol chemistry adopts in various disciplines, such as stereoselective catalysis or the biosynthesis of aromatic polyketides, illustrates its exceptional versatility. On the one hand, numerous aldol addition reactions reliably transfer the stereochemical information from catalysts into various valuable products. On the other hand, countless aromatic polyketide natural products are produced by an ingenious biosynthetic machinery based on arene‐forming aldol condensations. With the aim of complementing aldol methodology that controls stereocenter configuration, we recently combined these two tenets by investigating small‐molecule‐catalyzed aldol condensation reactions that stereoselectively form diverse axially chiral compounds through the construction of a new aromatic ring. Abstract : An arena for carbonyl compounds : Intrigued by the biosynthesis of aromatic polyketides, stereoselective arene‐forming aldol condensation reactions were investigated that lead to the formation of configurationally stable binaphthalenes, axially chiral amides and oligo‐1, 2‐naphthylenes. As this versatile strategy provides various rotationally restricted compounds with high enantioselectivity, it is expected to be useful in many areas of application.